2013
DOI: 10.1124/jpet.112.202275
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal Role of Mouse Mast Cell Protease 4 in the Conversion and Pressor Properties of Big-Endothelin-1

Abstract: The serine protease chymase has been reported to generate intracardiac angiotensin-II (Ang-II) from Ang-I as well as an intermediate precursor of endothelin-1 (ET-1), ET-1 (1-31) from Big-ET-1. Although humans possess only one chymase, several murine isoforms are documented, each with its own specific catalytic activity. Among these, mouse mast cell protease 4 (mMCP-4) is the isoform most similar to the human chymase for its activity. The aim of this study was to characterize the capacity of mMCP-4 to convert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 49 publications
4
22
0
1
Order By: Relevance
“…Mechanistically, it was shown that chymase inhibition led to a decrease in the content of TGFβ and MMP2 in the lungs, and it was demonstrated that chymase inhibition prevented effects of endothelin‐1. The latter observation is thus in agreement with a previous study where chymase was shown to be pivotal for the conversion of Big‐endothelin‐1 to endothelin‐1 . Chymase inhibition (using TY‐51469) has also been shown to dampen liver fibrosis in hamsters fed on a methionine‐ and choline‐deficient diet, and it was demonstrated that chymase inhibition attenuated the induction of angiotensin II and collagen expression in comparison with placebo‐treated animals .…”
Section: Targeting Mast Cell Function In Fibrosissupporting
confidence: 91%
See 1 more Smart Citation
“…Mechanistically, it was shown that chymase inhibition led to a decrease in the content of TGFβ and MMP2 in the lungs, and it was demonstrated that chymase inhibition prevented effects of endothelin‐1. The latter observation is thus in agreement with a previous study where chymase was shown to be pivotal for the conversion of Big‐endothelin‐1 to endothelin‐1 . Chymase inhibition (using TY‐51469) has also been shown to dampen liver fibrosis in hamsters fed on a methionine‐ and choline‐deficient diet, and it was demonstrated that chymase inhibition attenuated the induction of angiotensin II and collagen expression in comparison with placebo‐treated animals .…”
Section: Targeting Mast Cell Function In Fibrosissupporting
confidence: 91%
“…The latter observation is thus in agreement with a previous study where chymase was shown to be pivotal for the conversion of Big-endothelin-1 to endothelin-1. 230 Chymase inhibition (using TY-51469) has also been shown to dampen liver fibrosis in hamsters fed on a methionine-and choline-deficient diet, and it was demonstrated that chymase inhibition attenuated the induction of angiotensin II and collagen expression in comparison with placebo-treated animals. 231 In addition, chymase inhibition using various compounds has been demonstrated to reduce cardiac fibrosis and Ang II production in diabetic hamsters, 232 cardiac fibrosis after ischemia reperfusion injury, 233 silica-induced pulmonary fibrosis in mice, 234 CCl 4 -induced liver fibrosis in hamsters, 235 tubulointerstitial fibrosis in obstructed kidneys in hamsters, 236 cardiac fibrosis in rats subjected to ligation of the left anterior descending coronary artery, 237 cardiac fibrosis in cardiomyopathic hamsters 238 and cardiac fibrosis in dogs subjected to tachycardia-induced heart failure.…”
Section: Inhibitors Of Protease Activitymentioning
confidence: 99%
“…ET-1 is also a major factor involved in myocardial infarction pathophysiology and is a critical factor in pulmonary hypertension, a possible complication of heart failure ( Sakai et al, 1996 ). Finally our group demonstrated the role of mMCP-4 in the endogenous pulmonary synthesis of ET-1 in vivo ( Houde et al, 2013 ). Therefore, in light of the beneficial role of chymase inhibitors in other rodent models of heart failure, we hereby hypothesized that specific mMCP-4 activity repression would protect mice from PMI.…”
Section: Introductionmentioning
confidence: 94%
“…The closest mouse analog to human chymase, in terms of localization, substrate specificity and storage properties is mMCP-4 ( Pejler et al, 2010 ). Furthermore, chymase activity in the mouse heart is primarily due to mMCP-4 expression ( Houde et al, 2013 ). Cardiovascular targets of chymase in mice and humans include the activation of angiotensin-II (Ang-II), endothelin-1 (ET-1) and matrix metalloproteinase 9 (MMP-9) as well as the degradation of the matrix protein fibronectin ( Balcells et al, 1997 ; Houde et al, 2013 ; Semaan et al, 2015 ; Caughey, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chymase has the capability to produce ET-1 by cleaving the precursor peptide Big-ET-1 in vivo [58]. Chymase has also been reported to cleave known itch mediators such as interleukins 6, 13, and 33 (IL-6, IL-13, IL-33 [59,60]) as well as substance P and VIP [41][42][43].…”
Section: Mmcp4 and Et-1-induced Scratch Behaviormentioning
confidence: 99%